PROSES PERBAIKAN DENGAN REWINDING STATOR MOTOR INDUKSI TIGA FASA 380 V 75 KW DI PT. MESINDO TEKNINESIA - , MAWAHIB MAHMUD ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Induction motor is a kind of electrical machines which are widely used in industry. In industry, Induction motor is applied as one of the driving tool which is used to support the production process, , so that maximum care is needed to maintain the efficiency of induction motor and to maintain the continuity of the production process. One of the factors that affect the efficiency of the motor is the damage of winding insulation or the motor winding. In this internship the writer was doing final project study about 3-phase motor induction squirrel cage rotor with 75 KW power output, 380 Volt delta and a frequency of 50 Hz, at which these motors have occurred short phase to phase. Step of motor induction reparation are done by rewinding process. This process includes the record before the repair process, replace the burned winding, record after the repair process and test the motors running. In the process of reparation there are many measurements by using a Electrical apparatus Servise Association (EASA) standard.